The Role of Social Intelligence in Enhancing the Supply Chain and Talent Management Competencies According to the Goleman Model: A Survey Study in Kirkuk Governorate's Private Hospitals - Maysoon Abdullah Al-Shalmh (International Journal of Supply Chain Management, 2020)
Abstract- The study aims to provide an integrated practical and theoretical framework on the role of social intelligence in enhancing the competencies of supply chain and talent management according to the Golman model. Therefore, Al-Salam Private Hospital / Kirkuk was chosen as one of the service organizations in that province, which needs multiple studies in advanced and modern topics that would enhance Among the talents of talent management among the individuals working in the sample, as well as raise their performance when they have the ability to exploit the available creative minds they have the ability to manage talent in their work, and to add something new to the work of that organization in order to enhance these competencies to achieve a high level from U.S To perform, especially in service organizations, in an innovative way that achieves positive results, hence the problem of the study, which was formulated with a set of questions that aimed to identify the level of social intelligence in enhancing the competencies of talent management, and to determine the relationship of impact and the link between the dimensions of the study dimensions and to achieve that, a set of hypotheses was formulated , An intentional sample consisting of workers in the researched organization was chosen as it is their responsibility to achieve the best levels of performance by strengthening the talent management competencies of the researched organization, their number reached (40) represented in different specialties, where the questionnaire was approved as a key tool To obtain appropriate information in the field and analyze it using statistical means through programming (SPSS), the study reached a set of conclusions, the most important of which was (the presence of a significant correlation between the dimensions of social intelligence combined and the enhancement of talent management competencies in that researched organization) and in the light of those Conclusions The researchers presented a set of proposals that are important to enhance the competencies of talent management in that organization, the most important of which (the necessity of working on the issue of applying the dimensions of social intelligence by encouraging thinking based on its success can be adopted to enhance the competencies of EDA The talent of workers in the respondent organization).